2009
DOI: 10.1039/b818295g
|View full text |Cite
|
Sign up to set email alerts
|

Linking high anisotropy Dy3 triangles to create a Dy6 single-molecule magnet

Abstract: A unique Dy(III)(6) complex is created by linking of two Dy(III)(3) triangles, in which intramolecular ferromagnetic interactions and single-molecule magnetic behaviour have been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 214 publications
(73 citation statements)
references
References 25 publications
7
66
0
Order By: Relevance
“…Hence, we suggest it is the unreacted thiocyanate behaving as a weak base that is the most likely candidate to initiate the formation of the enolate. Hussain [13] and Perlepes [8] have used strong base to initiate the formation of enolates, but in the present work, we have observed similar results with much weaker bases.…”
Section: Mechanistic Considerationssupporting
confidence: 89%
See 2 more Smart Citations
“…Hence, we suggest it is the unreacted thiocyanate behaving as a weak base that is the most likely candidate to initiate the formation of the enolate. Hussain [13] and Perlepes [8] have used strong base to initiate the formation of enolates, but in the present work, we have observed similar results with much weaker bases.…”
Section: Mechanistic Considerationssupporting
confidence: 89%
“…This condensation reaction has been reported recently by Hussain et al [13] who found that a new aldol ligand was generated when o-vanillin reacted in the presence of Dy(III), potassium hydroxide and acetone.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Murugesu et al, as early as 2009, reported the first such example of a unique Dy III 6 complex formed by the coupling of two similar Dy III 3 triangles, in which intramolecular ferromagnetic interactions and singlemolecule magnetic behaviour was witnessed (Hussain et al, 2009). In an effort to create new-generation smarter lanthanide SMMs with large anisotropic barriers and also to grasp the inimitable properties of such systems, Ln 3 complexes were employed as building blocks to create larger SMMs by using the simple synthetic approach (Milios et al, 2006).…”
Section: Homonuclear Ln 6 Smmsmentioning
confidence: 99%
“…Notwithstanding the enormous inherent interest in SMMs, it was also understood that they could, in principle be developed for new technological applications following a strategy-based rational approach (Hussain et al, 2009;Hewitt et al, 2009;Long et al, 2011;Chen et al, 2011;Guo et al, 2011;Lin et al, 2012;Xue et al, 2012;Tian et al, 2012;Anwar et al, 2012;Habib et al, 2012). Entirely novel applications of SMMs have recently been envisaged, including the advancement in the field of molecular spintronics (Leuenberger et al, 2001;Coronado et al, 2004;Ardavan et al, 2007;Bouchiat et al, 2008;Bogani et al, 2008;Mannini et al, 2010;Urdampilleta et al, 2011;Katoh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%